2010
DOI: 10.1158/1078-0432.ccr-10-0093
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Single-Cell Network Profiles in Acute Myelogenous Leukemia Are Associated with Patient Response to Standard Induction Therapy

Abstract: Purpose Complete response to induction chemotherapy is observed in ~60% of patients with newly diagnosed non-M3 acute myelogenous leukemia (AML). However, no methods exist to predict with high accuracy at the individual patient level the response to standard AML induction therapy. Experimental Design We applied single-cell network profiling (SCNP) using flow cytometry, a tool that allows a comprehensive functional assessment of intracellular signaling pathways in heterogeneous tissues, to two training cohort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
70
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 50 publications
2
70
1
1
Order By: Relevance
“…Recent phospho-flow studies using adult AML samples have found an association between increased basal and induced pY-Stat3 and decreased likelihood of achieving remission. 13,15 We did not find an association between the magnitude of basal or induced pStats and clinical outcome. Our data instead revealed a significant association between the sensitivity of the ligand response and outcome, with increased sensitivity being significantly associated with better survival.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Recent phospho-flow studies using adult AML samples have found an association between increased basal and induced pY-Stat3 and decreased likelihood of achieving remission. 13,15 We did not find an association between the magnitude of basal or induced pStats and clinical outcome. Our data instead revealed a significant association between the sensitivity of the ligand response and outcome, with increased sensitivity being significantly associated with better survival.…”
Section: Discussioncontrasting
confidence: 54%
“…11,12 More recently, we and others have measured phosphorylated Stat proteins in AML samples by intracellular flow cytometry (phospho-flow). [13][14][15][16][17] This highly sensitive method yields quantitative information at the single-cell level.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 They are attractive agents for oncologic imaging, 28,29 but several difficulties must be overcome to achieve the necessary specificity and avidity for in vivo contrast. 30 The number of target antigens per cell is a defining factor in the successful application of mAbs for imaging applications.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] The association of SCNP data with in vivo acute myeloid leukemia (AML) chemosensitivity/chemoresistance 17 as well as FLT3R signaling deregulation 18 and applications in immunology 19,20 have been previously reported. Here the SCNP assay was first applied in an exploratory study to functionally characterize elements of the BCR signaling network and to assess their association with clinical and prognostic parameters with the goal of ultimately developing a clinically useful tool for the prediction of B-CLL progression and early (<3 years) TTFT in patients with early stage B-CLL.…”
Section: Introductionmentioning
confidence: 99%